Evolución y tendencias del empleo público en México : 1964-1988 - Blanco, Mercedes (El Colegio de México A.C., 1993)
The purpose of the article is to describe the dynamism of public employment in Mexico's central government administration during the past 25 years.This empirical delineation is based on the proposition that the Mexican government comprises several labor markets with highly differentiated characteristics, each with its own dynamic and mode of functioning. Thus, this article analyzes separetely the central administration, comprised basically of the government's secretariats, and the state-owned industries.Finally, given that the state acts in its role as employer the labor markets of this sector have a more direct relationship with the economic and political processes generated from within the state itself. As a result, the evolution and trends of employment in Mexico's central administration are closely tied to the political and economic orientation of each presidential administration.